“Innovative Methods for Teaching Fine Arts in Higher Education: Combining Flipped Classroom, Project-Based Learning, and Multimedia Tools” - Kodirov Obid Esonboy o‘g‘li (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores innovative teaching strategies for fine arts courses in higher education, combining flipped classroom methodology, project-based learning (PBL), and multimedia tools. The study examines how these approaches enhance students’ artistic perception, creative thinking, and aesthetic literacy. It also discusses pedagogical strategies to implement this integrated approach effectively, fostering student engagement, independent learning, and collaborative problem-solving in the context of fine arts education.